IMMU-19. Outcomes of Pediatric Patients with High-Risk CNS Tumors Treated with Multi-tumor associated antigen specific T cell (TAA-T) therapy: the ReMIND trial. (3rd June 2022) - Hwang, Eugene; Fortiz, Fernanda; Cruz, Russell; Geiger, Ashley; Grant, Melanie; Lang, Haili; Shibli, Abeer; Burnett, Sianna; Lazarski, Chris; Tanna, Jay; McCann, Chase; Hoq, Fahmida; et al.
Abstract: BACKGROUND: The ReMIND trial hypothesizes that autologous T-cells specific for three tumor-associated antigens (TAA) -WT1, PRAME, and survivin- will be safe and elicit anti-tumor immunity in pediatric patients with CNS cancer. METHODS: Patients (n=25) received autologous TAA-T for newly-diagnosed DIPG (Stratum A, up to 4x107/m2) or recurrent CNS malignancies (Stratum B, up to 8x107/m2) in this dose-escalation study (NCT03652545) and were monitored for toxicity and response. RESULTS: Autologous TAAT products were successfully manufactured from 28 patients. Using IFN-γ ELISPOT assay, 10/11 evaluable products had specificity for 1-3 TAAs. 25 patients received TAA-T (6 in Stratum A and 19 in Stratum B) and completed the 45-day safety monitoring period. Twenty-four (96%) had no dose limiting toxicities (DLT), but 1 (4%) patient with DIPG experienced a DLT related to potential immune-mediated pseudoprogression. Median overall survival for patients with DIPG (Stratum A) was 14 months (range, 6-32 months). Median progression-free survival (PFS) for Stratum B patients was 8 months (range, 2-26+ months), which exceeded their preceding median duration of disease stability of 2 months (range, 1-5 months). Plasma cytokine profiles demonstrated infusion-related immune cytokine responses. CONCLUSIONS: In summary, TAAT had a favorable toxicity profile (4%) especially compared to CAR-T therapy and may elicit anti-tumor immune responses that contribute to prolonged survival. Immunobiology studies and response assessments are ongoing for both strata. Based on these encouraging preliminary results, we have added a stratum that includes prescribed lymphodepletion pre TAA-T administration at a cell dose of 8x107/m2. Further, we plan to add an additional stratum to allow direct administration of TAA-T into the CNS via an Ommaya reservoir.